Karakterisasi Udang Air Tawar Anggota Genus Macrobrachium Bate, 1868 (Decapoda: Palaemonidae) dari Air Terjun Tegenungan, Gianyar, Bali Berbasis Data Morfologi dan Molekular - Wildan Ahmad Nabil; Rury Eprilurahman (Biogenesis: Jurnal Ilmiah Biologi, 2018)
Macrobrachium is one of prawn genera which has largest species number in family Palaemonidae, with some species of this genus being important commodity in aquaculture. Morphological characters for identification of this genus depend on environmental condition, growth phase, sex, and social dominance. This makes morphological identification on this genus quite difficult and tricky. Alternative approaches are required for better methods of Macrobrachium identification. DNA barcoding using 16S mitochondrial rRNA appears to be one promising method for Macrobrachium identification. This research aims to identify Macrobrachium from Tegenungan Waterfall using morphological and molecular analysis. Samples were taken from 4 sampling sites beneath the waterfall. All specimens were identified using several morphological identification methods. Specimen CR 07a and CR 10 were identified using molecular method. The molecular analysis utilized 16Sar (5’-CGCCTGTTTATCAAAAACAT-3’) as forward primer and 16Sbr (5’-CCGGTCTGAACTCAGAT-CACGT-3’) as reverse primer. From 11 specimens, 10 were identified as Macrobrachium. Specimen CR 07a was identified morphologically as M. horstii. According to BLAST analysis, specimen CR 10 was recognized as M. horstii with similarity up to 99% to GenBank specimens (JF310718.1 dan FM986616.1). Specimen CR 07a only reach 97% similarity to both GenBank specimens. Genetic distance analysis between specimen CR 07a and CR 10 assumed high genetic diversity, or even cryptic species indication in M. horstii population of Tegenungan Waterfall.